Ecopedagogy in Action: An Ethnographic Exploration of Environmental Preservation Strategies in Pesantren - Maslani Maslani; Wahyu Hidayat; Abdul Qadir; Asep Muhyidin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
The exploitation of gold mining, environmental degradation, and the evident impacts of global warming signal a societal lack of awareness regarding ecological and social hazards. Recognizing the significance of ecological awareness, educational institutions, particularly Islamic boarding schools, are mandated to contribute to the creation of environmentally conscious communities. This research employs a qualitative ethnographic approach to elucidate the practical strategies employed by Indonesian Islamic boarding schools in environmental preservation. The study encompasses four institutions: Islamic Boarding School Biharul Ulum, Agroecology, Bogor; Islamic Boarding School Daarul Falah Bogor; and Islamic Boarding School Ath-Thoriq, Garut. Findings reveal that all three Islamic boarding schools have cultivated environmental consciousness through ecopedagogy, engaging in activities such as planting productive trees within their premises and the surrounding communities. Ecopedagogy involves selecting superior seeds, planting, fertilizing, and harvesting. Additionally, these institutions partake in environmental conservation by raising livestock, including chickens, goats, cows, and fish. Rooted in the teachings of the Al-Qur'an and Hadith, ecopedagogy is delivered through face-to-face instruction, in-depth discussions, and practical field guidance. This ecopedagogical approach, aligned with Islamic teachings, showcases the commitment of these Islamic boarding schools to instilling environmental preservation values in their students, reflecting a comprehensive approach to ecological consciousness.